Revitalizing Civic Education in Higher Education : Student Perspectives, Identity, and Reconstruction Strategies - Subkhan, Muhamad; Komalasari, Kokom; Abdulkarim, Aim; Bestari, Prayoga (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to analyze student perceptions regarding civic education learning in tertiary institutions, student perceptions regarding their national identity as Indonesians, and considerations needed for the reconstruction of civic education in Higher Education. This study used a mixed method with a sequential exploratory approach. Data was collected through surveys and interviews. A total of 160 respondents were involved in the survey. Interviews were conducted with 3 senior lecturers who teach Civic Education courses at State Universities in Bandung. The data were analyzed using descriptive analysis techniques and verification through Structural Equation Modeling methods and Confirmatory Factor Analysis. The study results showed that the teaching of Civic Education must be able to build student interest through the application of teaching methods that are appropriate, creative, contextual, and in accordance with student needs. Civic Education learning must also be able to strengthen students’ awareness of the importance of national identity to prevent them from attitudes and behaviors inconsistent with the nation’s noble values. Civic education reconstruction efforts must be based on real problems faced by lecturers and students in Civic Education learning, especially by considering the clarity of goals, the focus of change, the challenges of citizenship in the global era, and the concrete situations that are developing in society. This study is needed to provide an appropriate basis for the formulation and implementation of the reconstruction of civic education to strengthen the Indonesian nation’s national identity.